In Search of Amrit Kaur : An Indian Princess in Wartime Paris - Sambuy, Livia Manera (London Chatto & Windus, 2023)
ur and terror, beauty and sorrow, In Search of Amrit Kaur is an engrossing detective story, a kaleidoscopic history lesson, and a moving portrait of mothers, lovers and daughters across the century, seeking personal freedom"
Including Illustration, Map, Bibliography And Index
Keywords: Amrit Kaur -- Biography